-3x+5=x+-5

Simple and best practice solution for -3x+5=x+-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x+5=x+-5 equation:


Simplifying
-3x + 5 = x + -5

Reorder the terms:
5 + -3x = x + -5

Reorder the terms:
5 + -3x = -5 + x

Solving
5 + -3x = -5 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
5 + -3x + -1x = -5 + x + -1x

Combine like terms: -3x + -1x = -4x
5 + -4x = -5 + x + -1x

Combine like terms: x + -1x = 0
5 + -4x = -5 + 0
5 + -4x = -5

Add '-5' to each side of the equation.
5 + -5 + -4x = -5 + -5

Combine like terms: 5 + -5 = 0
0 + -4x = -5 + -5
-4x = -5 + -5

Combine like terms: -5 + -5 = -10
-4x = -10

Divide each side by '-4'.
x = 2.5

Simplifying
x = 2.5

See similar equations:

| -130+3x=113- 6x | | x^2-2x+6=2x^2-6x-26 | | 9x-83=3x+67 | | 12m^2-32m+20=0 | | X=-x^2+3 | | 7x+5-3x-8=8x+6+5x-9 | | X^2+17x-168=0 | | 1.4x+x=-12 | | 1.6X=6.4 | | 3(x-1)=2(2x+1)-(x+5) | | -6(x+10)=-36 | | 8v^3+1= | | 3x+5x=13 | | -10x*2-24=0 | | 3x*2-12=0 | | 34+h=39 | | 6x^2=6+5x | | -21x=0 | | 2x+5x=28 | | 2x-5x=28 | | 241-2x=43x+21 | | 7-9x=73-23x | | (-16t^2)+31t-14=0 | | [2x+3]=3x+5 | | 0.2x+18.3=x-5.62 | | 3(2x-2.1)=4x-6.3 | | [2x-3]=11 | | -0.9x+4.32=-0.4x+6.32 | | -0.9x+4.32=0.4x+6.32 | | [x-1]=-8 | | 3(x+1.07)=2x | | y=-.5x+2 |

Equations solver categories